2020
DOI: 10.1002/ejic.201901314
|View full text |Cite
|
Sign up to set email alerts
|

A New Hexa‐TiIV‐Substituted Sandwich‐Type Polyoxotungstate: Hydrothermal Synthesis, Structure, and Oxidative Decontamination of Chemical Warfare Agent Simulant

Abstract: A new hexa-Ti IV -substituted sandwich-type silicotungstate, Na 2 (H 2 enMe) 4 [Ti 6 (μ-O) 9 (A-α-SiW 9 O 34 H 2 ) 2 ]·16H 2 O (1, enMe = 1,2-diaminopropane) has been synthesized under mild hydrothermal conditions and characterized by FT-IR spectroscopy, elemental analysis, thermogravimetric analysis, singlecrystal and powder X-ray diffraction. Compound 1 contains a dimeric polyoxoanion with two [A-α-SiW 9 O 34 ] 10-Keggin moieties sandwiching a trigonal-prismatic [Ti 6 (μ-O 9 )] 6+ cluster. The [a]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 93 publications
0
4
0
Order By: Relevance
“…1:3. We also carried out a lot of exploratory synthesis experiments to investigate the effects of the dosage of [ A -α-SiW 9 O 34 ] 10– and [α-P 2 W 15 O 56 ] 12– on the structure formation, but no other Ti-added structures constructed by mixed {SiW 9 } and {P 2 W 15 } were obtained, and we found that excessive amount of Keggin [ A -α-SiW 9 O 34 ] 10– yielded the previously reported sandwiched structure {Ti 6 (SiW 9 ) 2 } only including the {SiW 9 } fragments . From the view of the structure assembly of the title compound, {Ti 3 } 2 core-occupied {SiW 9 } is corner-shared, while {Ti 3 } 1 core-located {P 2 W 15 } is edge-shared; the configuration difference between {Ti 3 } 1 and {Ti 3 } 2 may be also the reason for preventing the increase of Keggin fragments in the structure of 1 .…”
Section: Resultsmentioning
confidence: 99%
“…1:3. We also carried out a lot of exploratory synthesis experiments to investigate the effects of the dosage of [ A -α-SiW 9 O 34 ] 10– and [α-P 2 W 15 O 56 ] 12– on the structure formation, but no other Ti-added structures constructed by mixed {SiW 9 } and {P 2 W 15 } were obtained, and we found that excessive amount of Keggin [ A -α-SiW 9 O 34 ] 10– yielded the previously reported sandwiched structure {Ti 6 (SiW 9 ) 2 } only including the {SiW 9 } fragments . From the view of the structure assembly of the title compound, {Ti 3 } 2 core-occupied {SiW 9 } is corner-shared, while {Ti 3 } 1 core-located {P 2 W 15 } is edge-shared; the configuration difference between {Ti 3 } 1 and {Ti 3 } 2 may be also the reason for preventing the increase of Keggin fragments in the structure of 1 .…”
Section: Resultsmentioning
confidence: 99%
“…To date, there have been some reports of POMs possessing the ability to catalyze the oxidation of organics in the presence of peroxide. [53][54][55][56][57][58][59][60] Herein, the catalytic activity of 1 was evaluated (Fig. 3a) under the conditions of methanol (4.0 mL), CEES (0.5 mmol), dodecane (internal standard), catalyst 1 (1.0 μmol), oxidizer H 2 O 2 (30%, 0.55 mmol), and room temperature.…”
Section: Communicationmentioning
confidence: 99%
“…Extensive work has demonstrated that detoxification of nerve agents through hydrolysis of labile P–X bonds (X = F, CN, S, etc.) is a promising route, while for the degradation of mustard gas, selective oxidation to sulfoxide is an effective approach. ,, Realistically, the CWAs deployed in war are usually unknown and deadly; hence, to efficiently prevent harm to human beings caused by CWAs, multifunctional catalysts that simultaneously detoxify various types of CWAs are highly desired. However, the different detoxification pathways make constructing versatile catalysts quite challenging.…”
Section: Introductionmentioning
confidence: 99%